Neuroinformatika a sdílení dat z lékařských zobrazovacích systémů - Klimek, Martin (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2010)
Předložená diplomová práce se zabývá problematikou skladování a sdílení primárních neurozobrazovacích dat. Práce obsahuje mj. organizační a informatické aspekty sdílení obrazových dat v multicentrických studiích s obrazy mozku z magnetické rezonance. Součástí práce je technické řešení sdílení dat včetně návrhu webového rozhraní pro práci s obrazovými daty v databázi.

The presented master's thesis deals with the issue of storing and sharing data from medical imaging systems. This thesis, inter alia, consists of organizational and informatics aspects of medical imaging systems data in multicentric studies containing MRI brain images. This thesis also includes technical design of a web-based application for image data sharing including a web interface suitable for manipulation with the image data stored in a database.
Neuroinformatics and sharing data from medical imaging systems
Keywords: Php; mysql; pacs; dicom; magnetická rezonance; multicentrický sběr dat; klinické registry; anonymizace; telemedicína; Php; mysql; pacs; dicom; mri; multicentric data collection; clinical registry/registries; anonymization; telemedicine